Some considerations on the measurement and evaluation of road roughness. (4th August 2014) - Kawamura, A.; Himeno, K.; Kasahara, A.; Shibazaki, R.; Kameyama, S.
Road roughness is a very important consideration in evaluating the condition of a given roadway, as it affects vehicles or vehicle passengers, e.g. ride comfort, safety, noise emission and operating cost factors. This research aims at measuring pavement surface profile and inquiring into methods for evaluating the serviceability of pavements that take into account the interaction between road surface and vehicle dynamics. This study is divided into two parts, starting with development of a new non–contact profilometer, which is capable of acquiring a huge volume of data at the normal vehicle speed. The new profilometer can be used to analyse even the macrotexture and obtain the roughness quite accurately. In the next part, correlations between the typical standards which relate to the evaluation of the road roughness are theoretically examined by the conventional mathematical model of the vehicle–tyre system. As a result, a schematic method that evaluates the road roughness synthetically is proposed.